Anisotropy of Full and Partial Anhysteretic Remanence Across Different Rock Types: 1—Are Partial Anhysteretic Remanence Anisotropy Tensors Additive?. Issue 2 (22nd February 2020) - Biedermann, Andrea R.; Jackson, Mike; Stillinger, Michele D.; Bilardello, Dario; Feinberg, Joshua M.
Abstract: Several types or grain sizes of ferromagnetic minerals can contribute to a rock's remanence and anisotropy of remanence. Each subpopulation may have a different fabric. Measuring anisotropy of partial anhysteretic remanent magnetization (ApARM) allows one to determine the anisotropy contribution of subpopulations with different coercivity distributions. Separating these contributions to remanence anisotropy can provide information about early versus late stages of deformation in fabric studies and is the basis for improved anisotropy corrections in paleomagnetic studies. Unfortunately, collecting multiple ApARM tensors on each specimen is time‐consuming and not often done. Measuring a smaller number of carefully chosen ApARM tensors and obtaining the remaining tensors of interest by tensor calculation would be more efficient. This can only be done, however, when ApARM tensors are additive. Here we investigate the additivity of ApARM tensors in a range of lithologies, by measuring a total of seven ApARM and anisotropy of anhysteretic remanent magnetization (AARM) tensors for each specimen, and comparing the tensors calculated from a combination of ApARM tensors to the corresponding measured AARM. Differences in principal directions between measured and calculated tensors are often smaller than the confidence angles of the measurements. Mean anhysteretic remanences are additive to within ±5%. The anisotropy degree varies by ±30% ( k ′) or ±0.15 ( P ), and the shape parameter U by ±0.4. These error limits will help to determine whether or not it is necessary to measure each ApARM tensor in future fabric or paleomagnetic studies, or if these tensors can be calculated from a smaller set of measurements. Key Points: Sets of 7 ApARM and AARM tensors measured for 93 samples to test additivity of ApARMs Principal directions are additive within confidence limit of measurement Mean pARMs additive to ±5%; error limits for anisotropy degree: ±30% ( k ′), ±0.15 ( P ), and shape: ±0.4